Sinergi Silang Pelaksanaan Program Kerja Malang Cerdas Baznas Kabupaten Malang Melalui Beasiswa “Satu Keluarga Satu Sarjana - Romadlon Chotib; Ulfatul Yaumi Zahro’ (Lembaga Pengembangan Kinerja Dosen, 2024)
The cross-synergy between Raden Rahmat Islamic University Malang and Baznas Malang Regency is implemented through the Malang Cerdas (Smart Malang) program. This work program aims to help children from underprivileged families continue their education, reaching children studying at various educational levels, from junior high school to higher education. Through cooperation via a Memorandum of Understanding (MoU) between Baznas Malang Regency and Raden Rahmat Islamic University Malang, this program strives to provide appropriate assistance so that these children can continue their education without obstacles. The program, named